Analisis Teknis dan Kajian Ergonomika berdasarkan Antropometri pada Penggunaan Traktor Tangan untuk Lahan Sawah (Anthropometry based Technical Analysis and Ergonomic Studies on Utilization of Hand Tractor for Farm Field: Anthropometry based Technical Analysis and Ergonomic Studies on Utilization of Hand Tractor for Farm Field - Endang Sulnawati; Sirajuddin H. Abdullah; Asih Priyati (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2016)
Purpose of this research was to analyzed technical utilization of hand tractors for farm field, analyze suitability of body dimension anthropometry data with dimension of hand tractors Yanmar Bromo Model V2 TF 85 MLY, and determine working load level by measuring operator’s pulse rate when using tractors for land preparation. This research conducted at Terara village, Terara district in East Lombok using field experimental method. Examined parameters, regard to technical test, were theoretical field capacity, effectivity and efficiency. Additional examined parameters based on ergonomic were anthropometry analysis and measurement of operator’s pulse rate. Results showed that the theoretical field capacity was 0.065 ha/hour and the effective field capacity was 0.025 ha/hour. Land processing efficiency was 38.38%; time lost during processing greatly affect the efficiency, where some of them caused by overlapping, slip, time for turning, and congestion (which share the greatest percentage of 30.35%). Results from anthropometry data measurement showed that the ergonomic dimensions for the tool are < 68.57 cm of gear level position from end of the handle, <95.27 cm of handle height position, <39.05 cm distance between grip, >8.82 cm handle length, and <9 cm distance of left and right turn lever. Tool’s dimension that already ergonomic, based on the results of anthropometry data measurement was position of gear lever from end of the handle with value of 68.57 cm and handle length with value of 8.82 cm. Operator’s working load level when using Yanmar Model TF 85 MLY Bromo V2 Tractor could be classified as moderate, with operator’s pulse rate of 100-125 sec/mnt.